Evaluation of Effect of Curcumin on Changes of Liver in Adrenalectomised Rats - H Morovvati (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2013)
ABSTRACTBACKGROUND AND OBJECTIVE: Curcumin has anti-oxidant effects and protects liver tissue. On the other hands, adrenal gland has several functions including carbohydrate metabolism, immunity and hematology and affects liver structure. Regarding to decreasing adrenal function in some pathologic conditions and consumption of curcumin as food additive the aim of present study was to evaluate histological and histomorphometrical changes in liver tissue after adrenalectomy and effect of curcumin on these changes.METHODS: In this study, 25 female Wistar rats were divided into 5 groups: control, treated with curcumin, adrenalectomised, adrenalectomised treated with curcumin and sham. Bilateral adrenalectomy was carried under anesthesia and muscles and skin were sutured. Curcumin was intraperitoneally administrated 100mg/kg for 21 days. At the end, the liver was sampled tissue sections were prepared and examined by light microscope. The number of injured hepatocytes, Kupffer and inflammatory cells was counted and evaluated. FINDINGS: The mean of injured cells was 21.6±0.5 and increased to 52.8±3.5 in adrenalectomized group (p<0.0001). The mean of Kupffer cells was 5.4±0.27 and increased to 15.8±3.2 in adrenalectomized group (p<0.0001). The number of these cells and liver changes was significantly decreased by curcumin.CONCLUSION: The results of this study showed that the curcumin can improve liver changes after adrenalectomy.